INNOVATIVE STRATEGIES TO OVERCOME LEARNING DIFFICULTIES AMONG THE YOUTH OF DESA TIMBANG LANGSA (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2024)
This research examines innovative strategies to overcome English learning difficulties among the youth of Timbang Langsa Village. Using a qualitative approach, this study aims to identify and analyze the effectiveness of three learning methods: the use of flashcards, handicrafts, and tutoring. The research is based on the premise that conventional approaches to English language teaching are often inadequate to meet the specific needs of youth in rural areas. Through participatory observation, in-depth interviews, and document analysis, this study reveals how these strategies can improve the interest, understanding, and English language skills of youth. The results show that the use of flashcards helps in vocabulary acquisition, handicraft activities increase active engagement in learning, while group discussions strengthen speaking skills and self-confidence. The findings provide valuable insights for educators and policy makers in designing more effective and contextualized English learning programs for rural communities.